ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI BERKARIR SEBAGAI KONSULTAN PAJAK - Wiranata, Ardi; Banjarnahor, Haposan (SCIENTIA JOURNAL, 2023)
The purpose of this study was to determine the effect of financial rewards, professionalrecognition, and labor market considerations on the interest of accounting students to workas tax consultant. The tests carried out in this study were descriptive analysis tests, dataquality tests, namely validity and reliability tests, classical assumption tests, namelynormality tests, multicollinearity tests, and heroscedasticity tests, multiple linear regressiontests, coefficient of determination tests, hypothesis tests, namely t tests and f tests. theresults of the study state that partially financial rewards, professional recognition, and labormarket considerations have a positive and significant effect on the interest of accountingstudents to have a career as a tax consultant. Simultaneously, financial rewards,professional recognition, and labor market considerations have a positive and significanteffect on accounting students' interest in a career as a tax consultant. The results of thecoefficient of determination with an Adjusted R Square value of 0.561 explain that the threeindependent variables in this study influence the dependent variable by 56.1% while theremaining 43.9% are influenced by other variables not present in this study